Review of Ravitch "National Standards" - Apple, Michael W. (Education Policy Analysis Archives, 1996)
I assume that Diane Ravitch is someone who is as deeply committed to a fair and socially just education as I am–even when our political and educational agendas may differ–I also assume that re-stratification and fostering the power of the conservative restoration is not what she wants either. Thus, I do urge you to read this book, but perhaps for different reasons: to see it as a cautionary tale and then to watch as the public policies that are justified under its rhetorical umbrella and that are actually implemented on the ground go in uncomfortable directions.